EFFECT OF WARM COMPRESSES DECOCTION OF GINGER TO DECREASE OSTEOARTHRITIS PAIN IN TECHNICAL SERVICES UNIT SOCIAL HOMES OF ELDERLY JOMBANG - . Widyastutik; . Hariyono; Ucik Indrawati (STIKES Insan Cendekia Medika Jombang, 2012)
Pain is an unpleasant feeling things that are perceived by osteoarthritis patients. Now to overcome the painpharmacological treatment alone is not enough, sh ouldalso be granted non- pharmacological treatment withherbal treatment, ginger contains anti - inflammatory and anti–inflammatory which proven to reduce pain.The purpose of this study was to determine the influence of warm compresses decoction of ginger todecreasethe pain of osteoarthritis. The types of research used approach one group pra-post test design. The samplestudied is 19 people with technique sampling rendom sampling with the inclusion and exclusion criteria. Theindependent variable is warm compresses decoction of ginger, while the dependent variable is the pain ofosteoarthritis with parameters ginger is boiled and used as a compress as well as facial expressions andranges pain to determine pain intensity,with ordinal scale will be used wilcoxon test to determine the effect ofthe experiment with criteria painless (0), mild pain (1-3),moderate pain (4-6), severe pain (7-9) and verysevere pain ( 10 ). Collecting data using instruments vas with a range of 1-10 who have tested the validityand reliabelitasnya then the data collected in the edit coding assessed the score later in the tabulation . Theresults showed before to warm ginger decoction obtained 4 mild pain (21%), pain was 12 people (63.2%), 3severe pain (15.8%) After compresses a change of 60%. The increase in painless 2 (10.5 %) , mild pain 7people (36.8%) , pain was 9 people (47.4%), severe pain one person (5.3%). Based on statistical testWilcoxon p-value of 0,000 (<0.05), which means H1 accepted. The conclusions of research there is effect ofwarm compresses decoction of ginger to decrease the pain of osteoarthritis.